Calculation of parameters of the vehicle according to changes in its trajectory - Баранов, Г. Л.; Коваленко, Ю. І. (Problems of Informatization and Control, 2008)
Considered process modeling the movement of high-speed vehicles and the analytical solutions of differential equations, which speeds up calculation